Project St[art] : o videojogo como forma de arte - Gouveia, João Ricardo Faria de (2019)
The present dissertation intends to explore the difficult and [yet] unexplained relationship between video games and art and, above all, to present the artistic potential of the medium through a dynamic approach related to the field of humanities rather than the usual line that focus on programming and design. The path chosen to the appreciation of video games as an art form begins by observing how contemporary society looks at video games and how they are apprehended by cultural institutions and art critics. Having, once, established the strangeness and the lack of knowledge of videogames in our culture and in the world of contemporary art, we decided to concentrate on the branch of ludology, hence launching the question of the origin of the act of play and the purpose of the creation of games in human nature and in society. Past this point, we present an analysis of multiple [attempts] definitions of the word “play” and “games” including/assembling various authors such as Brian Suton-Smith, Johan Huizinga, Roger Caillois, Jesper Juul and Miguel Sicart, with the purpose of developing a competent and practical grammar in the field of videogame research. Once established a grammar and conceptual protocol, the potential and artistic